Der Schmerz und seine Grenze : Eine phänomenologische Betrachtung chronischer Schmerzen - Wagner, Judith N (Schmerz (Berlin, Germany), 2025)
Chronic pain poses a significant global socio-medical challenge causing significant costs. It is only since the mid-20th century that pain syndromes have been considered diseases in their own right. According to the definition of the International Association for the Study of Pain, pain is a complex, context-dependent-and hence modifiable-phenomenon. The philosophical view on pain is no less multi-facetted and allows for a wide range of viewpoints. This analysis aims at a characterisation of pain including a-mainly phenomenological and enactivist-philosophical perspective. The discourse will be guided by the concept of the limit(s) of the lived body: what is the relationship between pain and the perception of the lived body's boundaries? Does a reciprocal influence exist? And may the perception be modified in order to reduce the patient's suffering? These musings will also clarify that neurosciences and philosophy are not competing sciences, but rather inform each other.
Keywords: filosofie lékařská; Lived body; Phenomenology; Pain Measurement; Transparency; Humans; Philosophy, Medical; Chronic Pain; Merleau-Ponty; lidé; Enactivism; měření bolesti; chronická bolest